Efficacy of Hypnotic Guided Imagery (HGI) Towards People with Depression - Karthik A/L Muthiah; Kwartarini Wahyu Yuniarti (Gadjah Mada Journal of Professional Psychology (GamaJPP), 2023)
It is well known that people with depressive illnesses are not very satisfied with their lives. There is a need to reduce depression’s symptoms in such ways so that the burden can be reduced. An intervention called Hypnotic Guided Imagery (HGI) was purposed to address this problem. Previously, HGI has been proven to be effective as a therapy to decrease depressive symptoms towards people with depression. The purpose of this study is to evaluate the efficacy of HGI in virtual setting as a psychotherapy substitute for individuals with depressive disorders. This study employs an experimental methodology and a control group with a pretest-posttest design. Participants included up to 10 Indonesians that suffers from depression that was diagnosed earlier by doctors. They were split into intervention and control groups and the PANAS-X and PHQ-9 were given to the participants before and after intervention as an instrument to test the efficacy of HGI. Hypothetically, HGI has the capability to decrease depressive symptoms among people with depression. Proven, HGI has an effect on both the reduction of some unpleasant emotions and the enhancement of other positive ones. This promising finding leads to the conviction suggesting HGI has many more to offer.